2022
DOI: 10.1111/ijfs.15930
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physicochemical quality and protein properties of porcine longissimus lumborum during dry ageing

Abstract: The present study investigated the effects of dry-ageing time on physicochemical quality and protein properties of porcine longissimus lumborum within 48 h of postmortem ageing. Results showed that appropriately prolonged dry-ageing time (24 and 36 h) had a positive effect on the tenderness, water-holding capacity, thermal stability and gel properties of meat, as evident from the decrease of shear force, dripping loss, cooking loss, T 2 relaxation time, enthalpy value and the increase in storage and loss modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The CIE b* in the PEFR group (0°C and –1°C) after 3 weeks of aging was higher than that after 2 weeks of aging, showing that an increase in the aging period increases the CIE b* of sous vide pork loin. Wang et al (2022) reported that as the aging period increases, oxidation of muscle also increases, leading to more CIE b*. Chroma was significantly higher in the raw meat samples than in the wet-aged group (p<0.05) and higher in the PEFR group than in the CR samples (p<0.05).…”
Section: Resultsmentioning
confidence: 96%
“…The CIE b* in the PEFR group (0°C and –1°C) after 3 weeks of aging was higher than that after 2 weeks of aging, showing that an increase in the aging period increases the CIE b* of sous vide pork loin. Wang et al (2022) reported that as the aging period increases, oxidation of muscle also increases, leading to more CIE b*. Chroma was significantly higher in the raw meat samples than in the wet-aged group (p<0.05) and higher in the PEFR group than in the CR samples (p<0.05).…”
Section: Resultsmentioning
confidence: 96%
“…Regarding muscle type, there are reports that the light scattering properties of some muscles are increased by postmortem protein degradation, which promotes an increase in the L* value [ 30 ]. Colored components are often formed by protein oxidation and degradation, and a high degree of protein oxidation and degradation causes meat discoloration during aging [ 37 , 38 ]. In our study, a* value was found to be higher in group B.…”
Section: Resultsmentioning
confidence: 99%
“…During aging, it is reduced to myoglobin by metmyoglobin reductase. However, metmyoglobin reductase activity gradually decreases with aging and the flesh color can change from red to brown [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations